Filantropi dan Strategi Dakwah terhadap Mualaf: Kolaborasi Mualaf Center Yogyakarta, Dompet Dhuafa, dan Rumah Zakat di Yogyakarta - Ari Dyah Sinta; M Falikul Isbah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2019)
Existing studies have explored philanthropy as fund management practices for economic empowerment of the poor, or building infrastructure such as hospitals, schools, and Islamic boarding schools. This paper portrays another aspect, the role and strategy of Islamic philanthropy organisations in dakwah movement among newly-converted (muallaf) in Yogyakarta. Dakwah activities are normally conducted by dai in mosques through regular sermons. However, that method was considered as less effective as the task of dai is seen to be accomplished when the muallaf recite shahadat. The data here is drawn from a fieldwork at Mualaf Center Yogyakarta (MCY), and its collaboration with Dompet Dhuafa and Rumah Zakat. This research aimed to explore new forms of action by philanthropic organisations in their use of public fund. Through a qualitative approach and a case study method at MCY, this research found that MCY was in partnership with Dompet Dhuafa dan Rumah Zakat in their work. MCY was in charge in supporting spiritual and psychological aspect of muallaf, while Dompet Dhuafa and Rumah Zakat were in charge in empowering the economic and welfare of muallaf. Before receiving such support, the muallaf faced difficulties in conducting Islamic teachings such as praying, fasting, and ablution. After receiving the support, they found easier in fulfilling those.